From genetic gain to economic gain: simulated growth and financial performance of genetically improved Pinus sylvestris and Pinus pinaster planted stands in France, Finland and Sweden. (24th February 2021) - Serrano-León, Hernán; Ahtikoski, Anssi; Sonesson, Johan; Fady, Bruno; Lindner, Marcus; Meredieu, Céline; Raffin, Annie; Perret, Sandrine; Perot, Thomas; Orazio, Christophe
Abstract: The translation of genetic gains into economic gains is important for evaluating the impact of using genetically improved forest reproductive material (FRM) in the forest sector. However, few studies based on European forests have been published to date. Here, we analyse the stand-level wood production and financial performance of planting genetically improved FRM in even-aged planted forests focusing on four European case studies with advanced breeding programme material and different management contexts: Scots pine ( Pinus sylvestris L.) in southern Finland, central Sweden and central France, and maritime pine ( Pinus pinaster Ait.) in southwestern France. The growth of improved stands was simulated using species-specific growth models by incorporating two levels of expected genetic gains (present and next generations of seed orchards, varying from 7 to 40 per cent depending on the breeding programme) into the estimated mean annual volume increment over a rotation (m 3 ha −1 yr −1 ). For each level of genetic gain, we tested the plantation of improved FRM managed with two silvicultural scenarios (maintaining the standard baseline rotation and thinning regime vs shorter rotation through the earlier achievement of the recommended felling criteria) in comparison with the plantation of the reference unimproved material (absence of genetic gain) managed according to the standard silvicultural regime. The use of improved FRM resulted in a larger financial performance in terms of soil expectation value (SEV € ha −1, discount rate 3 per cent) than planting unimproved reference material in all case studies and silvicultural scenarios for different wood price contexts (SEV gain from +20 to +190 per cent depending on the genetic and silvicultural context). The challenges associated with the economic assessment of realized gains from genetically improved FRM are discussed. We argue that silvicultural guidelines should be adapted to the use of improved FRM in order to gain better financial performance and flexible silvicultural response of planted forests to future environmental and socio-economic changes.